Assessment of Barriers and Facilitators to Institutional Delivery in an Urban Area of Delhi: A Community Based Cross- Sectional Study - Sharma, Aarti; Raj, Vipin; Tiwari, Nitin; Kumar, Devendra; Bachani, Damodar (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2023)
Background: Since motherhood is one of the most important roles in the life of any women and needs utmost priority in dealing with the delivery time, so the study was conducted with the aim to explore data related to antenatal check-ups and associated barriers for not availing the services and the reasons for the health facility preferred (Govt. or Private). for which a semi structured, pretested interview schedule was administered to all the study subjects for obtaining the relevant details. Subjects and Method: The community based cross sectional study was carried out in Palam area of west Delhi from January to December 2016 with a sample size was of 250 and analysis was done using Statistical Package for Social Sciences (SPSS version 20). The independent variables under study were social demographic characteristics, while dependent variables were the different reasons cited for preferring home delivery by the study subjects. Results: Among the women interviewed, 60.8% women preferred a Govt. health care facility for antenatal services, 14.4% visited only private health care facility for complete antenatal services whereas 22.4% were those who availed antenatal service from both Government as well as Private health care. Nearly two-third (65.2%) of the deliveries took place in Government facility, whereas around 25% preferred private facility for the delivery and remaining 10% were home deliveries. Conclusion: The reasons need to be explored by systematic continuous monitoring and supervision of services including periodic beneficiaries view point on services being provided, re-orientation of service providers and counselling of pregnant women in order to achieve hundred percent institutional deliveries or by skilled birth attendant. Keywords: barriers, facilitators, institutional delivery. Correspondence: Devendra Kumar. Department of Community Medicine, Autonomous State Medical College, Firozabad, Uttar Pradesh, India. Email: devendrakumar224224@gmail.com. Mobile: +919818102046.